Estimating the Value of Higher Education Financial Aid: Evidence from a Field Experiment - Christian Belzil; Arnaud Maurel; Modibo Sidibé (Institute of Labor Economics (IZA), 2020)
Using data from a Canadian field experiment on the financial barriers to higher education, we estimate the distribution of the value of financial aid for prospective students. Our results point out that a considerable share of prospective students are affected by credit constraints. We find that most of the individuals are willing to pay a sizable interest premium above the prevailing market rate for the option to take up a loan, with a median interest rate wedge equal to 6.8 percentage points for a 1,000 loan. The willingness-to-pay for financial aid is highly heterogeneous across students, with preferences and in particular discount factors, playing a key role in accounting for this variation.
Keywords: I22; I23; J24; 330; higher education financing; time and risk preferences; field experiment